Public Relation Internship at Pitchforks Partners - Rehal, Anmol (ATLAS SkillTech University, 2024)
This executive summary provides an overview of Public Relation internship at Pitchfork Partners, where we get to know everything in public relation The internship encompassed a diverse range of tasks, including social media research, daily media updates, automobile industry and consumer research, enabling the intern to gain invaluable skills and insights. Pitchfork Partners A strategy consulting firm with a focus on strategic communication and reputation management. They are devoted to assisting companies in establishing, preserving, and protecting their reputations. Public relations are the practice of managing and disseminating information from an individual or an organization to the public to influence their perception. Some of its functions include building up the Brand Image, strengthening relationship with Communities, promoting brand value, developing content, etc As Bajaj Auto has assigned its communications mandate to Pitchfork Partners Strategic Consulting. The agency will be responsible for elevating the brand’s corporate and brand reputation, along with managing its public relations and communication across all domestic verticals. It will also support the brand’s thought leadership initiatives. Media relations, content production, events, social media management, crisis communications, and reputation management are a few examples of activities that fall under the PR umbrella. Building trust and credibility with the organization's stakeholders is the aim of public relations.
Project Report on Public Relation Internship at Pitchforks Partners (2022-24) Under the Guidance of Dr. Tapish Panwar